WIN 51711-dependent mutants of poliovirus type 3: evidence that virions decay after release from cells unless drug is present. - Mosser, A G (1993)
Twenty-two spontaneous mutants of the Sabin strain of poliovirus type 3 were selected for drug resistance by plating on HeLa cell monolayers in the presence of WIN 51711, an uncoating inhibitor. When replated in the presence and absence of drug, two classes of mutants were observed; mutants displayed either a drug-dependent or a non-drug-dependent phenotype, in the proportion 14:8. Non-drug-dependent mutants plaqued with equal efficiency in the presence or absence of drug. By contrast, drug-dependent mutants made no plaques in the absence of drug, except for revertants. In single-step growth curve experiments, however, drug-dependent mutants grew as well in the absence of drug as in its presence. This paradoxical behavior of dependent mutants was traced to extreme thermolability at 37 degrees C (12- to 30-s half-life) in the absence of drug. Thermolability was exhibited only after the virus was released from the cell, implying the presence of a cell-associated protective factor, possibly pocket factor. Thus, in the absence of a thermostabilizing drug, drug-dependent mutants decayed too rapidly after release to permit spread in the plaque assay. The thermodecay product was shown to consist of 135S particles lacking VP4.